Vagino-Laparoscopic Conservative Strategy of Hysterectomy in Indicated Cases of Severe Pelvic Endometriosis Followed by 24 Months of Depot-Medroxyprogesterone Acetate Therapy— A Symptom-Solving Treatment Model to Ease Surgical Challenges - Purohit R; Sharma JG; Meher D; Samy MM (Dove Medical Press, 2023)
Ramkrishna Purohit,1 Jay Gopal Sharma,1 Devajani Meher,1 Mohammed Mahmoud Samy2 1Department of Obstetrics & Gynaecology, Purohit General Hospital, Bargarh, India; 2Department of Obstetrics & Gynaecology, Ainshams University, Cairo, EgyptCorrespondence: Ramkrishna Purohit, Department of Obstetrics & Gynaecology, Purohit General Hospital, Shakti Nagar, Bargarh, Odisha, 768028, India, Tel + 91-6646-234403, 234468 ; +91-94370 54403, Fax +91-6646-231597, Email ramkrishnapurohit@hotmail.comPurpose: To demonstrate the long-term outcome of a symptom-solving treatment model (SSTM).Patients and Methods: An observational study was carried out between June 2016 and December 2022 in our private setup on consecutive candidates of hysterectomy for severe pelvic endometriosis. Candidates were treated by the SSTM, which constitutes a systematic vagino-laparoscopic conservative strategy of hysterectomy with preservation of the ovary or ovaries followed by 24 months of postoperative depot-medroxyprogesterone acetate (DMPA) therapy. Cases were followed up to December 2022, 2.5 years beyond the last hysterectomy in May 2020.Main Outcome Measures: Relief of endometriosis-associated symptoms and prevention of recurrence in the long term.Results: Symptomatic relief of endometriosis-related pain, such as cyclical dysmenorrhoea, pelvic pain, dyschezia, and vaginal pain, occurred in all 68 (100%) cases from the next expected date of menstruation. None of the cases showed a recurrence of endometriosis-related pelvic pain; overall, 37 (54.41%) cases crossed 4- 6 years, and 31 (45.58%) cases crossed 2.5- 4.0 years following the hysterectomy operation. Four (5.88%) cases had non-endometriotic pelvic pain. None of the cases required repeat surgery or had any major side effects or complications due to DMPA. No major perioperative complications were observed. The results were achieved without the requirement of challenging extensive retroperitoneal laparoscopic dissection, ureterolysis, and rectum surgeries.Conclusion: This SSTM can be an option in indicated cases of severe pelvic endometriosis to provide symptom relief and prevent the recurrence of endometriosis-associated pelvic pain in the long term.Keywords: severe pelvic endometriosis, vagino-laparoscopic hysterectomy, relief of endometriosis-associated pelvic pain, recurrence of endometriosis-associated pelvic pain, DMPA therapy following hysterectomy, hysterectomy with ovarian conservation, symptom-solving treatment model